A quantitative performance management framework for assessing omnichannel retail supply chains. (May 2019) - Adivar, Burcu; Hüseyinoğlu, Işık Özge Yumurtacı; Christopher, Martin
Abstract: This study proposes a performance management framework with a roadmap to success and evaluates successful retailers. We provide comparative analysis of brick-and-mortar versus omnichannel retail supply chains and propose comprehensive performance metrics categorized with respect to four competitive dimensions (sustainability, efficiency and effectiveness, responsiveness, flexibility) and seven perspectives (customers, operations, sourcing, finance, information sharing and information technology, transportation, environment). Two customer-centric frameworks and a statistical model are developed to analyze the characteristics of successful omnichannel retail supply chains. The quantitative analysis shows that physical stores are a critical component of omnichannel strategy for many retailers. From a practical perspective, our frameworks provide guidelines and metrics to be used for assessing the success of omnichannel retailers. The comparative analysis of the top 25 U.S. retailers provides additional insights for critical success components in transition to omnichannel retailing.